Women with Symptomatic Preterm Birth Have a Distinct Cervicovaginal Metabolome - Ghartey, Jeny; Anglim, Laura; Romero, Julie; Brown, Amy; Elovitz, Michal A. (American Journal of Perinatology, 2017)
Objective The objective was to determine if women with symptoms of preterm labor who ultimately have a spontaneous preterm birth (sPTB) have a distinct cervicovaginal (CV) metabolome compared with women who deliver at term.Study Design A nested case–control study of women presenting with symptoms of preterm labor was performed. CV fluid was collected from women between 22 and 336/7 weeks' gestation. The CV metabolome was compared between women with sPTB (n = 20) and women who delivered at term (n = 30). Global biochemical profiles were determined using ultraperformance liquid chromatography/tandem mass spectrometry. Welch's two-sample t-test was used to identify metabolites that differed significantly. Level of significance was defined as p ≤ 0.05.Results Eighty-eight percent of women were African-American and none had a prior history of sPTB. A total of 301 metabolites were identified in CV fluid. Thirty metabolites were significantly different in women with preterm birth compared with term birth. Two metabolites (mannitol and methyl phosphate) were significantly upregulated, and the remaining 28 metabolites were significantly downregulated and consisted of medium chain-fatty acids and collagen degradation markers.Conclusion The CV metabolome is significantly altered among women who present with preterm labor symptoms and ultimately have a sPTB.
Keywords: spontaneous preterm birth; cervicovaginal metabolome; vaginal microbiota; metabolomics